The morphometric-anatomical parameters of the intercondylar notch in adult knee of Serbian population - Jeremic, Dejan; Zivanovic-Macuzic, Ivana; Vulovic, Maja; Kovacevic, Marija; Minic, Milos (Education and Research in Health Sciences, 2022)
Objective: The aim of this investigation was to examine normal intercondylar notch morphometry in Serbian population and to determine whether there are sex differences in anatomical parameters of the intercondylar notch among asymptomatic subjects without structural change. Method: The study included MR images of 90 patients (45 men and 45 women) receiving a 1,5-T knee scan at our radiological institute after the approval from ethics committee, which were taken in the period from 2010 to 2017. The knee was placed in neutral position, and MR images were obtained using conventional spin echo techniques. The morphology of the intercondylar notch (U- shaped and A-shaped notch) was measured for each knee. Results: The measurements of parameters for intercondylar notch geometry were obtained by analyzing coronal MR images. U-shaped intercondylar notch was found with 46 patients (51.2%) and A-shaped intercondylar notch with 44 (48.8%). There was no significant difference in the shape incidence in Serbian population (p>0.05). According to the notch width index (NWI) and the Notch shape index (NSI) criteria, we found U-shaped intercondylar notch with 24 men and 22 women and A-shaped intercondylar notch with 23 men and 21 women. There was no significant difference in incidence between the genders (p>0.05). Conclusion: We concluded that for all examined anatomical parameters of the intercondylar notch there were no significant differences in Serbian population. According to our findings in this study, we concluded that there was no sexual dimorphism for anatomical parameters of intercondylar notch in Serbian population.